An empirical investigation of factors influencing Islamic websites use and their positive impact from Muslim user perception - Aliyu, Mansur; Mahmud, Murni; Md Tap, Abu Osman; Mohammad Nassr, Rasheed (Universiti Kebangsaan Malaysia (UKM), 2013)

(untitled)
The global explosion of the Internet and its continued use by individuals, Islamic organisations and scholars to spread their teachings and activities has witnessed massive growth over the years. However, it appears that online Islamic content and activities may lack credibility and authority, since the websites are anonymous and uncontrolled in comparison to the traditional face-to-face method of seeking Islamic knowledge. This paper empirically investigates the content and Islamic factors that influence use of Islamic websites by Muslim users and consequently the positive impact of those websites on their behaviour. The study examines the perception of online Muslim users on the impact of various content and Islamic factors on the use of Islamic websites and its subsequent effect on user behaviour. An exploratory factor analysis was conducted using SmartPLS 2.0; this produced seven factors, namely: content credibility, content objectivity, content reliability, Islamic identity, Islamic services, Islamic symbols, and Islamic ethical values. The findings of the study suggest that both Islamic and content factors are significant indicators for influencing Islamic website use. On the other hand, the findings show that out of the seven factors extracted, only the content reliability factor and Islamic ethical values factor have a weak influence on the use of Islamic websites. In summary, the study indicates that the use of Islamic websites has a positive impact on users towards being better practising Muslims. Finally, the research model and empirical results provide valuable indicators for the direction of future research and also suggest guidelines for developing Islamic websites that will successfully meet users’ needs and expectations.